Psychological aspects of patients with breast cancer depending on the presence of visible postoperative defect - A. D. Zikiryakhodzhaev; M. V. Ermoschenkova; N. A. Sirota; B. A. Fetisov (Исследования и практика в медицине)
Objective. The study of coping behavior of patients with breast cancer (I, II stages) in the postoperative period with «externally visible postoperative defect".Materials and methods. We studied the psychological characteristics of 35 patients with breast cancer (I, II stage), who underwent radical mastectomy, women were characterized in the postoperative period as "externally visible postoperative defect" ("e.v.p.d."), 35 patients with breast cancer (I, II stage) who underwent ablative and reconstructive plastic surgery, women were characterized in the postoperative period as "without an externally visible postoperative defect" ("without an e.v.p.d.").The results and conclusions. The results of the study of women in both groups indicate that the patients are moderately using coping strategies for coping with the disease, preferring the strategy of "problem resolution" and "search of social support". Patients with breast cancer "with externally visible postoperative defect in comparing with patients with breast cancer "without an externally visible postoperative defect" often use positive religious coping in coping with the disease. The group of women with «externally visible postoperative defect" usually operate with negative religious coping. Both groups of women focused on the perception of social support. In a greater degree of social support they perceive from family and significant for them. Women with breast cancer and "externally visible postoperative defect” compared with women “without an externally visible postoperative defect" are not satisfied with your opportunities, have a feeling of weakness, doubt ability to evoke respect, sympathy, understanding and approval from others. They seek to change, doubt their self-worth, willing to put themselves in the guilt of their mistakes, failures, have low self-esteem. The group of patients with breast cancer "with externally visible postoperative defect" has an external locus of control. Patients with breast cancer "with externally visible postoperative defect" basically give a fatalistic sense to their disease. Indicators of anxiety and depression was significantly higher in the group of female patients with breast cancer "with externally visible postoperative defect" and located in the "clinically significant clinically significant anxiety and depression."